Aztreonam Combinations with Avibactam, Relebactam, and Vaborbactam as Treatment for New Delhi Metallo-β-Lactamase-Producing Enterobacterales Infections—In Vitro Susceptibility Testing - Małgorzata Brauncajs; Filip Bielec; Marlena Malinowska; Dorota Pastuszak-Lewandoska (Pharmaceuticals, 2024)
Antimicrobial resistance is a major global health issue. Metallo-β-lactamases (MBL), in particular, are problematic because they can inactivate all classes of β-lactams except aztreonam. Unfortunately, the latter may be simultaneously inactivated by serine β-lactamases. The most dangerous known MBL is New Delhi Metallo-β-lactamase (NDM). This study aimed to test the in vitro susceptibility to aztreonam in combination with novel β-lactamase inhibitors (avibactam, relebactam, and vaborbactam) in clinical strains of Enterobacterales NDM which is resistant to aztreonam. We investigated 21 NDM isolates—including Klebsiella pneumoniae, Escherichia coli, and Citrobacter freundii—which are simultaneously resistant to aztreonam, ceftazidime/avibactam, imipenem/relebactam, and meropenem/vaborbactam. MICs for aztreonam combinations with novel inhibitors were determined using the gradient strip superposition method. The most effective combination was aztreonam/avibactam, active in 80.95% strains, while combinations with relebactam and vaborbactam were effective in 61.90% and 47.62%, respectively. In three studied strains, none of the studied inhibitors restored aztreonam susceptibility. Aztreonam/avibactam has the most significant antimicrobial potential for NDM isolates. However, combinations with other inhibitors should not be rejected in advance because we identified strain susceptible only to tested combinations with inhibitors other than avibactam. Standardization committees should, as soon as possible, develop official methodology for antimicrobial susceptibility testing for aztreonam with β-lactamase inhibitors.